The association of genotype polymorphisms with vascular access patency in hemodialysis patients. Issue 1 (May 2019) - Chen, Chun-Fan; Lin, Chih-Ching
Some hemodialysis patients suffer from repeat dysfunction of dialysis vascular access and need procedures of angioplasty, thrombectomy, and even temporary catheter use. Why these patients are vulnerable to vascular access dysfunction and how to improve its patency are imperative to be discovered. Traditional risk factors for vascular access function had been widely investigated but could not fully explain this question. Several genotype polymorphisms were demonstrated to increase the incidence of cardiovascular disease and might also be linked to higher risk of vascular access dysfunction. As the major causes of arteriovenous access thrombosis are hypercoagulable status and arteriovenous access stenosis, the investigated genes mainly focus on the mediators of the coagulation cascade, inflammatory process, and endothelial dysfunction. The reported polymorphisms of genes significantly associated with arteriovenous access dysfunction included genes encoding methylene tetrahydrofolate reductase, coagulation factors, heme oxygenase-1, matrix metalloproteinase, transforming growth factor-β1, tumor necrosis factor-α, vascular endothelial growth factor-A, renin-angiotensin-aldosterone system, and protein methyl transferase. However, further prospective study is indispensable to elucidate the association between the genotype polymorphisms and the outcome of vascular access. More and more therapeutic options that focus on genotype polymorphisms may generate a great benefit to the patency of vascular access of uremic patients.